2015
DOI: 10.1007/s13538-015-0301-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermal Lens Effect in Gold Nanoparticle-Doped Lyotropic Liquid Crystal by Nanoparticle Clustering Probed by Z-Scan Technique

Abstract: This work presents an experimental study of the thermal lens effect in Au nanoparticles-doped lyotropic liquid crystals under cw 532 nm optical excitation. Spherical Au nanoparticles of about 12 nm were prepared by Turkevich's method, and the lyotropic liquid crystal was a ternary mixture of SDS, 1-DeOH, and water that exhibits an isotropic phase at room temperature. The lyotropic matrix induces aggregation of the nanoparticles, leading to a broad and a red-shifted surface plasmon resonance. The thermal nonlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…𝜀 𝐹 𝜀 𝐹 −ℏ𝜔 (13) Where d is the distance between the center of adsorbed molecule and the image plane.…”
Section: Fig 1 Geometry Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…𝜀 𝐹 𝜀 𝐹 −ℏ𝜔 (13) Where d is the distance between the center of adsorbed molecule and the image plane.…”
Section: Fig 1 Geometry Of the Problemmentioning
confidence: 99%
“…It was considered in the majority of experimental [13][14][15] and theoretical works [11,12,[16][17][18][19] that the width of SPR line varies smoothly with the variation of the dielectric permittivity of the environment. It was established in the work [20] in the frameworks of the finite equations method that the width of SPR line oscillates as the dielectric permittivity function of the environment.…”
Section: Introductionmentioning
confidence: 99%
“…An important contribution of the thermal conductivity of a nanouid is the aggregation of the NPs. It has been observed that aggregation of metallic or plasmonic NPs leads to both an enhancement of the conversion of electromagnetic energy to heat [19,20] and of thermal conductivity [21]. Particularly, ferrouids display a strong enhancement of the thermal conductivity due to the formation of aggregates by dipolar interaction under a magnetic eld [22 24] and without an external eld at high concentrations [25].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, studied in [13] was formation and behavior of surface plasmon resonance in thermotropic calamitic liquid crystals, and in [14] -strain in time of thermomechanical nematic liquid crystal elastomer. Effect of ANP on lyotropic liquid crystals similar to the body fluids was investigated in [15]. It was shown that lyotropic matrix induces aggregation of nanoparticles, which leads to a red shift of the surface plasmon resonance.…”
Section: Introductionmentioning
confidence: 99%